Entre fragmentos: os ditos e não-ditos das ruínas patrimoniais - Pontes, Anna Maria de Lira (2010)
This study covers the ruins heritage and how these are handled in politics formulated globally and nationally. Therefore, it became necessary initial theoretical reflections on the theme itself and its own conception. Due to the complexity in the notion of protected ruins. In the possible limits of preservation, we search initially the theoretical study to understand more about the concept that currently are titled ruins, but that alone already arouses several and different interpretations. Imbued with this theoretical apparatus, we can, then, study its politics around such differential protection of patrimony looking for, from such correlation, to recognize the role of the ruins in the contemporary context of protection and utilization of historical patrimony under its legal aspect. Thus, we seek the reflection through analysis of documents formulated on this topic, available globally and nationally, released by competent organizations. And, also, practical actions of IPHAN in Brazil. And, from these studies, we also understand the implications and current needs of the protected ruins in the context both of preservation of these monuments as analyzing usage, more specifically, the ruins preserved by IPHAN in Paraíba, they are: the ruins of the Almagre, Cabedelo; the ruins of Forte Velho, Santa Rita and, finally, the ruins of the Church of Tambaú (Igreja de Tambaú) and Casa da Pólvora, João Pessoa.